Accounting Standards for the Public and Non-profit Organization in the USA - Jana Ištvánfyová; Ladislav Mejzlík (European Financial and Accounting Journal, 2010)
Governmental accounting in the US has undergone significant changes and with it the complexities of preparing financial statements for governmental entities increased. The GASB, Governmental Accounting Standards Board establishes the rules for reporting financial information for non-profit and public entities. The most important objective of governmental accounting and financial reporting is accountability. The GAAP hierarchy for governments consists of four levels, each having a varied degree of authority.
Keywords: M40; 650; Governmental accounting standards board; GASB; Financial reporting; Not-for-profit organizations; Public sector; GAAP